2014
DOI: 10.1167/14.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Contrast dissimilarity effects on crowding are not simply another case of target saliency

Abstract: Previous studies have shown crowding alleviation when target and flankers similarity is reduced. However, in the case of contrast dissimilarity, the findings were inconsistent. This study examined the effect of stimulus contrast, particularly contrast dissimilarity, on both overall performance under crowded conditions and the critical distance-the spatial extent of crowding. To this end, we measured orientation identification of a rotated T presented with and without flankers. Target contrast was either the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
(66 reference statements)
6
23
0
Order By: Relevance
“…That is, temporal crowding does not seem to be caused by lack of attention. This attentional alleviation of temporal crowding is similar to the attentional alleviation of spatial crowding that was previously found in our lab (Rashal & Yeshurun, 2014;Yeshurun & Rashal, 2010). In these studies, we have used very similar visual attentional cues and found attentional improvement of overall accuracy as well as attentional decrement of the flanker-target distance at which the flankers no longer affect performance (i.e., reduction of the size of the critical distance).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…That is, temporal crowding does not seem to be caused by lack of attention. This attentional alleviation of temporal crowding is similar to the attentional alleviation of spatial crowding that was previously found in our lab (Rashal & Yeshurun, 2014;Yeshurun & Rashal, 2010). In these studies, we have used very similar visual attentional cues and found attentional improvement of overall accuracy as well as attentional decrement of the flanker-target distance at which the flankers no longer affect performance (i.e., reduction of the size of the critical distance).…”
Section: Discussionsupporting
confidence: 87%
“…It was suggested in these studies that attention alleviates spatial crowding by reducing the region over which information is integrated. This hypothesis is supported by the finding that the attentional decrement of the critical distance does not interact with the decrement in critical distance brought about by increasing the target contrast, because this finding rules out an alternative account suggesting that the attentional effect on spatial crowding reflects contrast enhancement (Rashal & Yeshurun, 2014). Currently, we cannot determine whether the similar pattern of attentional effects found with spatial and temporal crowding reflects similar attentional processes in time and space.…”
Section: Discussionmentioning
confidence: 90%
“…In the fixation conditions, our results suggest that crowding can be modulated by the absolute and relative contrasts of the target and flanker, replicating previous accounts [29,31,4952]. Previous research showed that increasing the target contrast alleviates crowding whereas reducing it results in stronger crowding [29,49,50]. Stronger crowding when the flankers have higher contrast than the target compared with when they all have the same contrast cannot be explained by target--flanker similarity because it predicts weaker crowding for the former case.…”
Section: Discussionsupporting
confidence: 88%
“…This reduction could be significant, since contrast is known to modulate the size of the crowding zone (Coates et al, 2013b). Several studies have examined how differences in contrast between the target and flankers affect the critical spacing of crowding (Chung et al, 2001; Kooi et al, 1994; Pelli et al, 2004; Rashal and Yeshurun, 2014), or have used threshold contrast as the dependent variable to study crowding (Levi et al, 2002; Strasburger et al, 1991). However, a complete characterization of the relationship between overall stimulus contrast and the extent of the crowding zone is lacking, although there are several clues from the literature.…”
Section: Introductionmentioning
confidence: 99%